Review of Decreased IL-6 Levels in SOPK-Insulin Resistant Rats fed a Low Carb High Protein Diet - Hany Puspita Aryani; Dwi Retno Wati; Sugiyanta Sugiyanta (STIKES Adi Husada, 2023)
Polycystic ovary syndrome with insulin resistance (SOPK-RI) is caused among endocrine disorders with an incidence rate of 5-10% that occurs in women of reproductive age. Characteristics of polycystic ovary syndrome are found anovulation, hyperandrogens, polycystic ovarii and impaired insulin sensitivity involving proinflammatory increases in several inflammatory cytokines including interleukin-6 (IL-6). Increased inflammatory cytokines in women with SOPK-RI found health problems there is fat accumulation in adipocyte tissue such as in an obese person, metabolic syndrome and type 2 diabetes. The purpose of this study was to determine the effect of a low-carbohydrate high-protein diet on changes in IL-6 levels in SOPK-RI model mice. Laboratory experimental research, namely post test only control group design. Consisting of three groups, namely, the negative control group (K-) as a normal group did not get treatment; The positive control group (K+) of the SOPK-insulin resistance model mice were given standard feed, and the treatment group (P) of the SOPK-insulin resistance model mice were given a low-carbohydrate high-protein diet (CTR) with a composition of 40% carbohydrate and 30% protein. The study lasted for 48 days, using serum ELISA examination on IL-6 levels. The average results of IL-6 levels, namely the K- = 0.358 group, K+ = 0.387 and P = 0.442 and obtained different IL-6 levels of significance value p = 0.002 with a low-carbohydrate high-protein diet in SOPK - RI rats showed a significant difference (p < 0.05) between the control group and the treatment group. Significantly reduced IL-6 levels in SOPK-RI model mice. A low-carb, high-protein diet may be considered as a dietary modality in women with SOPK-insulin resistance. Further research is needed to better determine the other modulators involved in this mechanism in more detail.